The wreckage of philosophy : Carlo Michelstaedter and the Limits of Bourgeois Thought - Cangiano, Mimmo (Toronto Italian studies., 2019)
"The work of Carlo Michelstaedter (1887-1910) is the first analysis of modernist philosophy as analyzed in strict connection with social changes in mass society. Revealing how Michelstaedter was able to unveil the relations between pivotal early-modernist philosophies and social restructurings, The Wreckage of Philosophy examines the ongoing processes of "specialization," "rationalization," and "atomization." The Wreckage of Philosophy points out how Michelstaedter connected the main theoretical expressions of Modernism with the decisive social transformations of the early-twentieth century, taking into consideration the key players of modernist philosophy, such as Friedrich Nietzsche, Henri Bergson, Ernst Mach, and William James. By following Michelstaedter's analysis and strategies, The Wreckage of Philosophy focuses on several intertwined issues: the distinct philosophical positions within the modernist area; the connections between philosophy and modernist literature; the relations between intellectual positions and social upheavals; and the early-twentieth century links among traditional philosophy, critique of language, and epistemology of technique. A complete analysis of Carlo Michelstaedter's philosophy, this book analyses his work as one of the sharpest investigation of the practical and ideological mechanisms that assure social consent."--